2022
DOI: 10.1038/s41467-022-32314-z
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactones are chemoattractants for host tropism in Orobanchaceae parasitic plants

Abstract: Parasitic plants are worldwide threats that damage major agricultural crops. To initiate infection, parasitic plants have developed the ability to locate hosts and grow towards them. This ability, called host tropism, is critical for parasite survival, but its underlying mechanism remains mostly unresolved. To characterise host tropism, we used the model facultative root parasite Phtheirospermum japonicum, a member of the Orobanchaceae. Here, we show that strigolactones (SLs) function as host-derived chemoattr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 78 publications
1
20
0
Order By: Relevance
“…In addition, we found that exogenous strigol, an SL, enhanced the germination of P. japonicum in nitrate-deficient conditions. In combination with our previous findings demonstrating that steps for host tropism are promoted by exogenous SLs and attenuated by ambient nitrogen sources, 17 we propose a model for determining whether P. japonicum can live independently or become a parasite.…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…In addition, we found that exogenous strigol, an SL, enhanced the germination of P. japonicum in nitrate-deficient conditions. In combination with our previous findings demonstrating that steps for host tropism are promoted by exogenous SLs and attenuated by ambient nitrogen sources, 17 we propose a model for determining whether P. japonicum can live independently or become a parasite.…”
Section: Introductionsupporting
confidence: 60%
“…Since seed germination is often enhanced by light-induced biosynthesis of the phytohormone gibberellin, 24 we germinated P. japonicum seeds in dark conditions to exclude the effects of light. The germination percentage on agar without any supplementary nutrients was lower than that on the 1/2 MS agar with sucrose, 22 a nutrient-rich medium that has been used for P. japonicum germination 17 , 18 , 23 ( Figure 1a ). We noticed that the germination percentage of P. japonicum seeds in the dark was only around 50% even on 1/2 MS with sucrose, in contrast to around 100% germination of A. thaliana seeds in the dark.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations